The Importance of Teaching Elementary Students About the History of Science Development - Baiti, Nanda Nurul; Amin, Muhammad; Aini, Saripah; Salminawati, Salminawati (Jurnal Basicedu, 2023)
Science provides real change for the development of human life, including a scientific approach in the learning process in schools. This study aims to describe the urgency of studying the history of science development for elementary age children. This type of research includes qualitative with the method of literature study. Data sources are quoted from credible pages in the form of Google Scholar and Sinta. The research data includes books, articles, proceedings and final assignments (thesis, or dissertation) that are relevant to the research topic. To test the validity of the data, the researcher cross-checked the research materials. The results of this study concluded that the history of the development of science is important to give to children of primary age, because it is useful for increasing children's insight and internalizing the value of respect for history to children from an elementary age. The implications of this research teach children about basic concepts, history, and the benefits of science in everyday life.